Labour pain with remifentanil patient‐controlled analgesia versus epidural analgesia: a randomised equivalence trial. (27th June 2016) - Logtenberg, SLM; Oude Rengerink, K; Verhoeven, CJ; Freeman, LM; van den Akker, ESA; Godfried, MB; van Beek, E; Borchert, OWHM; Schuitemaker, N; van Woerkens, ECSM; Hostijn, I; Middeldorp, JM; et al.
Abstract : Objective: To distinguish satisfaction with pain relief using remifentanil patient‐controlled analgesia (RPCA) compared with epidural analgesia (EA) in low‐risk labouring women. Design: Randomised controlled equivalence trial. Setting: Eighteen midwifery practices and six hospitals in the Netherlands. Population: A total of 408 pregnant women at low risk for obstetric complications initially under the care of primary‐care midwives. Methods: Women randomised before active labour to receive analgesia with RPCA or EA, if requested. Main outcome measures: Primary outcome was satisfaction with pain relief measured hourly using a visual analogue scale and summed as area under the curve (AUC). Secondary outcomes were overall satisfaction with pain relief, pain intensity scores during labour, mode of delivery, and maternal and neonatal outcomes. Results: We randomised 418 women, of whom 409 could be followed for the primary endpoint. Analgesia was received by 46% (94/203) in the remifentanil group and 37% (76/206) in the epidural group. The AUC for satisfaction with pain relief was 32 in the remifentanil group and 31 in the epidural group (mean difference −0.50; 95% CI −6.8 to 5.9). Among women who actually received analgesia, these values were 23 and 35, respectively (mean difference −12; 95% CI −22 to −1.5). Secondary outcomes were comparable. Conclusions: In low‐risk labouring women, we could not demonstrate equivalence between a strategy with RPCA to EA with respect to satisfaction with pain relief assessed during the total duration of labour. However, once applied satisfaction was higher in women who received epidural analgesia. Tweetable abstract: Satisfaction with pain relief is higher in women receiving epidural analgesia compared with Remifentanil PCA. Tweetable abstract: Satisfaction with pain relief is higher in women receiving epidural analgesia compared with Remifentanil PCA.